2016
DOI: 10.1007/s40596-016-0531-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Branched-Narrative Virtual Patients for Interprofessional Education of Psychiatry Residents

Abstract: Although there are important methodological limitations to this study including a small sample size and absence of a comparator group, this pilot study supports the use of branched-narrative virtual patients in an interprofessional education series for advanced learners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…However, opportunities for interprofessional working appear to be limited in community and outpatient settings, a finding reflected in the vestibular rehabilitation setting [ 11 ]. In psychiatry and pharmacology, the use of virtual learning environments has been shown to be effective at facilitating interprofessional learning at a post-graduate level [ 48 , 49 ]. This study indicated that physiotherapists may be open to online professional development and training facilitated through the Chartered Society of Physiotherapy (CSP) website and iCPS learning platform.…”
Section: Discussionmentioning
confidence: 99%
“…However, opportunities for interprofessional working appear to be limited in community and outpatient settings, a finding reflected in the vestibular rehabilitation setting [ 11 ]. In psychiatry and pharmacology, the use of virtual learning environments has been shown to be effective at facilitating interprofessional learning at a post-graduate level [ 48 , 49 ]. This study indicated that physiotherapists may be open to online professional development and training facilitated through the Chartered Society of Physiotherapy (CSP) website and iCPS learning platform.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, use of discussion panels, standardized patients (ie, patient actors), and virtual patient technology have all been investigated as means of evaluating trainee communication and interaction with unique patient populations, all with encouraging results. 3 , 15 - 17 Given the current state of transgender health education in pharmacy schools, coverage of even basic information using any combination of these tools presents a significant learning opportunity, for example, the use of appropriate terminology and importance of asking patients for their preferences. Similarly, students should understand that being transgender is not a psychiatric illness; rather, gender dysphoria, or the marked discomfort associated with the incongruence of one's gender biology and gender identity, is a psychiatric disorder according to the Diagnostic and Statistical Manual of Mental Disorders , 5th edition.…”
Section: Discussionmentioning
confidence: 99%
“…With the internet being readily available and devices easily portable, there has been a positive impact on continuity of education among medical trainees (Moran, Briscoe and Peglow, 2018). Virtual learning has also emerged as an excellent approach for teaching residents (Jayakumar et al, 2015;Wilkening et al, 2017). Lessons learned from the virtual learning arena, such as creating a positive learning environment can be transferred to the learning environment in clinical care (Chick et al, 2020).…”
Section: Introductionmentioning
confidence: 99%